Both perforin and FasL are required for optimal CD8 T cell control of autoreactive B cells and autoantibody production in parent-into-F1 lupus mice(1) - Soloviova, Kateryna (Clin Immunol, 2018)
To test the relative roles of perforin (pfp) vs. FasL in CTL control of autoreactive B cell expansion, we used the parent-into-F1 model of murine graft-vs.–host disease in which donor CD8 CTL prevent lupus like disease by eliminating activated autoreactive B cells. F1 mice receiving either pfp or FasL defective donor T cells exhibited an intermediate short-term phenotype. Pairing of purified normal CD4 T cells with either pfp or FasL defective CD8 T cell subsets resulted in impaired host B cell elimination and mild lupus like disease that was roughly equivalent in the two experimental groups. Thus, in addition to major roles in tumor and intracellular pathogen control, pfp mediated CD8 CTL killing plays a significant role in controlling autoreactive B cell expansion and lupus downregulation that is comparable to that mediated by FasL killing. Importantly, both pathways are required for optimal elimination of activated autoreactive B cells.